Subcellular Carrier-Based Optical Ion-Selective Nanosensors - Carregal Romero, Susana; Montenegro Martos, Jose María; Parak, Wolfgang; Rivera_Gil, Pilar (Frontiers in Pharmacology, 2012)
In this review we discuss two systems based on nanotechnology for real-time sensing of biologically relevant analytes (ions or other biological molecules) inside cells in a non-invasive way.